1976
DOI: 10.1007/bf00220682
|View full text |Cite
|
Sign up to set email alerts
|

Subsarcolemmal mitochondria and capillarization of soleus muscle fibers in young rats subjected to an endurance training

Abstract: Rats, 6 weeks old, were subjected to a program of endurance running for 3, 6 and 12 weeks. 0.5 to 0.8 mum thick sections of Epon embedded soleus muscles were studied with morphometric methods. In cross-sections the area occupied by subsarcolemmal mitochondria was independent of the age, but was 53% higher after 12 weeks of training. The mean depth of the zones with subsarcolemmal mitochondria increased only 15% to about 0.9 mum. Thus, the subsarcolemmal mitochondria showed a pronounced spreading at the muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(41 citation statements)
references
References 69 publications
2
37
0
1
Order By: Relevance
“…Mitochondria residing in the perinuclear region of the cell have been suggested to generate ATP that drives mitochondrial metabolism close to the nucleus. In contrast, it has been hypothesized that IFM supply ATP for contraction, whereas SSM are involved primarily in the provision of ATP for active transport of electrolytes and metabolites across the sarcolemma (89,96,111,118). Although these postulations have not been definitively determined experimentally, they are consistent with the concept that the spatial location of a given mitochondrion is reflective of the processes in which it supplies ATP and the given locale in which it resides.…”
Section: Structural and Functional Differencesmentioning
confidence: 89%
“…Mitochondria residing in the perinuclear region of the cell have been suggested to generate ATP that drives mitochondrial metabolism close to the nucleus. In contrast, it has been hypothesized that IFM supply ATP for contraction, whereas SSM are involved primarily in the provision of ATP for active transport of electrolytes and metabolites across the sarcolemma (89,96,111,118). Although these postulations have not been definitively determined experimentally, they are consistent with the concept that the spatial location of a given mitochondrion is reflective of the processes in which it supplies ATP and the given locale in which it resides.…”
Section: Structural and Functional Differencesmentioning
confidence: 89%
“…Morphological and functional differences in IMF and SS mitochondria have been reported in rodent skeletal muscle (18). It has been suggested that the IMF and SS mitochondria have different functions related to metabolic compartmentalization (1,19,25). Some have also suggested that these two populations are at different stages of biogenesis (15).…”
mentioning
confidence: 99%
“…Other investigations failed to confirm this in experimental animals (Parizkova, Wachtlova & Soukupova, 1972;Muller, 1976) or humans (Saltin, Blomqvist, Mitchell, Johnsson, Wildentahl & Chapman, 1968;Hermansen & Wachtlova, 1971). These conflicting observations might be explained by an age-dependent response of capillaries to training, but to our knowledge no study on the effect of age on changes in the capillary vasculature of the skeletal muscle following training has been made.…”
Section: Introductionmentioning
confidence: 83%
“…Brodal et at. (1977) and Andersen & Henriksson (1977) reported an increase in the mean number of capillaries in contact with each fibre in trained human beings, whereas Muller (1976) found no such change in young rats subjected to endurance training. An increased capillary density in skeletal muscle has been reported in variously aged rats (Tittel et al 1966;Parizkova et al 1972) and human beings (Andersen, 1975;Andersen & Henriksson, 1977;Brodal et al 1977) subjected to endurance training.…”
Section: Capillary Increase In Skeletal Musclementioning
confidence: 96%